Optimizing SAP Systems: Advanced Monitoring and Automation Techniques for Enhanced Performance - Arun kumar Malli Sundararaman Jayaprakash, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores comprehensive strategies for optimizing SAP systems through advanced monitoring and automation techniques, emphasizing the critical role these approaches play in enhancing system performance and operational efficiency. The article examines the evolution of monitoring technologies, particularly focusing on the integration of artificial intelligence capabilities in modern SAP environments. It explores the implementation of various automation frameworks, analyzing their impact on system reliability, maintenance workflows, and operational efficiency. The article delves into the transformation of SAP platform architecture in the cloud era, addressing crucial aspects of scalability, flexibility, and integration strategies. Through detailed analysis of implementation methodologies and best practices, the article demonstrates how organizations can establish robust monitoring frameworks and optimization procedures. The article also evaluates the business impact of these implementations and explores future technological considerations, providing insights into emerging trends and innovations in SAP system optimization. This comprehensive approach offers valuable insights for organizations seeking to enhance their SAP system performance while preparing for future technological advancements.
Keywords: SAP System Optimization; Artificial Intelligence Monitoring; Cloud Integration; Automation Frameworks; Performance Management